Reprogramming of regulatory T cells in inflammatory tumor microenvironment: can it become immunotherapy turning point? - Liu, Jinming; Zhang, Biao; Zhang, Guolin; Shang, Dong (Frontiers in Immunology, 2024)
Overcoming the immunosuppressive tumor microenvironment and identifying widely used immunosuppressants with minimal side effects are two major challenges currently hampering cancer immunotherapy. Regulatory T cells (Tregs) are present in almost all cancer tissues and play an important role in preserving autoimmune tolerance and tissue homeostasis. The tumor inflammatory microenvironment causes the reprogramming of Tregs, resulting in the conversion of Tregs to immunosuppressive phenotypes. This process ultimately facilitates tumor immune escape or tumor progression. However, current systemic Treg depletion therapies may lead to severe autoimmune toxicity. Therefore, it is crucial to understand the mechanism of Treg reprogramming and develop immunotherapies that selectively target Tregs within tumors. This article provides a comprehensive review of the potential mechanisms involved in Treg cell reprogramming and explores the application of Treg cell immunotherapy. The interference with reprogramming pathways has shown promise in reducing the number of tumor-associated Tregs or impairing their function during immunotherapy, thereby improving anti-tumor immune responses. Furthermore, a deeper understanding of the mechanisms that drive Treg cell reprogramming could reveal new molecular targets for future treatments.